Drivers for the Willingness of Small and Medium Enterprise in Implementing Halal Supply Chain Management - Azly Muhamed, Ariff; Nizam Ab Rahman, Mohd; Rosmawati Che Mohd Zain, Che (International Journal of Engineering and Technology, 2019)
This study investigates the role of consumer concern, supplier readiness, and government initiative in determining the willingness of halal SME to deploy halal SCM.  The hypotheses were assessed by using mail survey conducted in Malaysia in 2017. The empirical data use 172 data obtained from small and medium enterprise. Reliability and validity of the item is assessed through Cronbach alpha and factor analysis. To test the hypotheses, structural equation modelling by partial least square was adopted. The study finds that consumer concern plays a crucial role in determining the willingness to implement halal SCM. The supplier readiness can play important role in influencing halal SME to implement halal SCM. Finally, this study revealed that the important of government initiatives is significantly influenced halal SME to implement halal SCM in the operational activity.